Students acceptance and challenges of online learning during Covid-19 pandemic in higher education institution in Malaysia / Muhammad Majid ... [et. al] - Majid, Muhammad; Ramli, Mohamad Faizal; Mohammad, Noorita; Badyalina, Basri (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Since March 2020, the outburst of COVID-19 has caused universities in Malaysia to close their operations. Hence, Malaysian universities have to initiate online learning. However, there are some negative effects of online learning towards students’ motivation, performance and mental health. Moreover, a crucial point for lecturers is to understand the students’ acceptance and challenges of online learning in order to reduce the negative effect of online learning. Thus, this study intended to investigate the acceptance and challenges of online learning among students during COVID-19 pandemic. Responses were obtained from 320 undergraduate students from one of universities in Johor, Malaysia. The findings explained that students faced challenges on social issues, such as lack of communication among them, lack of group discussion and they feel isolated during online learning which affect the learning process. Besides, most of the respondents surveyed reported moderate levels of online learning acceptance. This study recommends universities to improve on their infrastructure and talent capital to improve the online learning acceptance and reduce challenges faced by students.